Book review: Moss, Jeremy. 2015: Climate Change and Justice. (July 2019) - Martens, Karel
Moss, Jeremy. 2015: Climate Change and Justice. Cambridge: Cambridge University Press. 253 pp. 12 chapters. £84.75 (Hardcover). ISBN 978-1-107-09375–1